"They Love Me, They Love Me Not": An IRT‐Based Investigation of the Child Parental Acceptance‐Rejection Questionnaire with a Japanese Sample. (11th May 2021) - Aktar, Rumana; Sugiura, Yuko; Hiraishi, Kenji
Abstract: This study aimed to (a) devise the Child PARQ (Child Parental Acceptance‐Rejection Questionnaire), Japanese version (Child PARQ‐J), and evaluate its construct validity; (b) select the best items for developing a shorter version; and (c) assess the reliability and validity of the shortened Japanese Child PARQ (Child PARQ‐J‐SF). The sample consisted of 603 Japanese adolescents (61% boys), aged 12–15 years ( M age = 13.95 years, SD = 0.85 years). Data were collected online by a research company using the Child PARQ‐J, the Japanese version of the World Health Organization's Well‐Being Index (WHO‐5‐J), and the Sense of Authenticity Scale (SOAS). Confirmatory factor analysis confirmed the proposed four‐factor model for the Child PARQ‐J. Use of the item response theory approach resulted in identical 18‐item versions of the Child PARQ‐J‐SF for both parents. Structural equation modeling demonstrated the predictive validity of the Child PARQ‐J‐SF for adolescents' sense of authenticity and well‐being. The Child PARQ‐J is a robust measure in the Japanese context, and the Child PARQ‐J‐SF is a promising tool for researchers to use for quick assessments or in studies involving multiple constructs.